Identification of stable reference genes and differential miRNA expression in Sri Lankan type 2 diabetes mellitus patients: a cross-sectional study - Palihaderu, Palihaderu Arachchige Dineth Supasan; Mendis, Balapuwaduge Isuru Layan Madusanka; Premarathne, Jayasekara Mudiyanselage Krishanthi Jayarukshi Kumari; Dias, Wajjakkara Kankanamlage Ruwin; Yeap, Swee Keong; Ho, Wan Yong; Dissanayake, Arosha Sampath; Rajapakse, Iyanthimala Harshini; Karunanayake, Panduka; Senarath, Upul; Satharasinghe, Dilan Amila (Frontiers in Endocrinology, 2025)
IntroductionType 2 Diabetes mellitus is a major global health concern. MicroRNA plays an important role in regulating pancreatic beta cells as well as peripheral insulin signaling. This study aimed to identify reference microRNA s in type 2 Diabetes mellitus plasma and validate two target microRNAs among a Sri Lankan population with type 2 diabetes mellitus.MethodsThis is a cross-sectional experiment. A total of fifty-three (N = 53) non-hemolyzed plasma samples from individuals with type 2 diabetes mellitus were selected to evaluate stability, in comparison to thirty-eight (N = 38) normoglycemic non-hemolyzed plasma samples. Initially, the stability of four candidate reference microRNAs (hsa-miR-16-5p, hsa-miR-425-5p, hsa-miR-191-5p, and hsa-miR-22-5p) was assessed. Stability was analyzed using the geNorm and BestKeeper algorithms. The relative expression changes of hsa-miR-29a-3p and hsa-miR-375-3p in the plasma of the same samples were evaluated using the validated reference microRNAs. The selected regulatory microRNAs were directly linked with type 2 diabetes mellitus pathogenesis and proved to be upregulated in type 2 diabetes mellitus plasma and serum.Results and discussionThe expressions of miR-16-5p and miR-191-5p were not stable between the two groups, miR-22-5p and miR-425-5p levels were found to be stable. A significant upregulation of hsa-miR-29a-3p and hsa-miR-375-3p was observed in type 2 diabetes mellitus patients compared to normoglycemic individuals (p ≤ 0.05). This was the first study to claim hsa-miR-425-5p and hsa-miR-22-5p as stably expressed reference microRNAs in type 2 diabetes mellitus patients. Sri Lankan type 2 diabetic patients also had increased hsa-miR-29a-3p and hsa-miR-375-3p levels. However, large and well-matched sample studies were suggested to ensure that these microRNAs can be used as type 2 diabetes diagnostic markers in Sri Lanka.